Comparative study between vaginal isosorbide mononitrate and misoprostol for induction of cervical ripening prior to surgical evacuation of first trimester embryonic demise - Dhillon, Amrit Pal Kaur; Shergill, Harbhajan Kaur; Yadav, Pawan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective: To compare the efficacy & safety of Nitric Oxide (NO) donor, isosorbide mononitrate (ISN) to that of misoprostol, applied vaginally as tablets for cervical ripening prior to suction evacuation of first trimester embryonic demise. Methods: This is a prospective, randomized, double blind controlled trial conducted at tertiary level teaching hospital. 50 women with first trimester embryonic demise with closed cervix requiring suction evacuation were divided randomly into two groups of 25 women each. In group A, tab. isosorbide mononitrate 80 mg and in group B, tab. misoprostol 400 µg was applied vaginally. Both the drugs were repeated every three hourly up to a maximum of four doses or until reaching cervical dilation of 8 mm. Cervical dilatation was assessed at baseline & every three hours after each dose. A set of questionnaire was used for the appearance of side effects. Once 8 mm cervical dilatation achieved, suction evacuation was done. Total volume of blood lost at suction evacuation was measured. Results: Frequency of doses, induction to ripening interval & intra operative blood loss was significantly higher with isosorbide mononitrate as compared to misoprostol. Headache & palpitation were main side effects of isosorbide mononitrate. The percentages of successful & failed inductions were comparable in both the groups. Conclusions: Misoprostol is better cervical dilator prior to suction evacuation in first trimester embryonic demise with minimal side effects which are acceptable to the patient.